The New Work of Composing - Cheryl Ball (Utah State University Press/ Computers and Composition Digital Press, 2012)
The New Work of Composing is a book-length collection whose purpose is to examine the complex and semiotically rich challenges and opportunities posed by new modes of composing, new forms of rhetoric, new concepts of texts and textuality, and new ways of making meaning. In particular, this book explores how digital media are shaping our understanding of scholarly projects within composition studies, including the need to reconsider print-centric conceptions of composing; theorize and illustrate new digital genres and interrogate definitions of authorial identity; consider how digital media change our understanding of (virtual and scholarly) space and place and allow new possibilities for embodiment; explore political implications of using new media in scholarship. Twelve chapters that respond to these objectives were solicited from participants of the 2008 Thomas R. Watson Conference on Rhetoric and Composition and were reviewed by the book's editors. The book includes a foreword by N. Katherine Hayles and responses to the themes above written by Marilyn Cooper, Paul Prior, Diana George, and Andrea Lunsford. Authors include established scholars in digital writing studies and digital humanities, as well as new voices.